Establishment of multiple pesticide biodegradation capacities from pesticide‐primed materials in on‐farm biopurification system microcosms treating complex pesticide‐contaminated wastewater. Issue 7 (2nd September 2014) - Sniegowski, Kristel; Springael, Dirk
Abstract BACKGROUND On‐farm biopurification systems (BPSs) treat pesticide‐containing wastewater at farms by biodegradation and sorption processes. The inclusion of pesticide‐primed material carrying a pesticide‐degrading microbial community is beneficial for improving biodegradation, but no data exist for treating wastewater containing multiple pesticides, as often occurs on farms. In a microcosm set‐up, an examination was carried out to determine whether multiple pesticide degradation activities could be simultaneously established in the matrix of a BPS by the simultaneous inclusion of different, appropriate pesticide‐primed materials. The microcosms were fed with a mixture of pesticides including the fungicide metalaxyl and the herbicides bentazon, isoproturon, linuron and metamitron, and pesticide‐degrading activities were monitored over time. RESULTS The strategy immediately provided the microcosms with a multiple pesticide degradation/mineralisation capacity, which improved during feeding of the pesticide mixture. Not only did the degradation of the parent compound improve but also that of the produced metabolites and compound mineralisation. The time to achieve maximum degradation/mineralisation capacity depended on the pesticide degradation capacity of the pesticide‐primed materials. CONCLUSIONS The data obtained show that the addition of pesticide‐primed materials into the matrix of a BPS as an approach to improve biodegradation can be extended to the treatment of pesticide mixtures. © 2014 Society of Chemical Industry